Effect of rain induced scintillation on Ku-band satellite link in tropical region - Dao, Hassan; Islam, Md. Rafiqul; Zuhairi, Megat Farez Azril; Megat Mohamed Noor, Megat Norulazmi; Sayed Hussin, Sayed Aziz (2014)
Scintillation data was collected from MEASAT3 for one year. This paper presents the scintillation statistics for dry (non-rain) and wet (rainy) conditions. Scintillation statistics are represented by scintillation intensity and amplitude distributions. Wet scintillation or scintillation during rain is obviously higher than dry scintillation (clear-sky scintillation).